The Effects of Knowledge, Religiosity Value, and Attitude on Halal Label Reading Behavior of Undergraduate Students - Simanjuntak, Megawati; Dewantara, Muhammad Mardi (ASEAN Marketing Journal, 2021)
Halal label is a label on food that justified according to Islamic law, qualified and did not harm our health. The purpose of this research was to analyze the effect of intrinsic factors (individual characteristics and family characteristics), extrinsic factors, knowledge, religiosity and the attitude towards behavior of reading the halal label on food products of undergraduate students. This study used cross sectional study with survey method. The research involved 400 students of Bogor Agricultural University that were chosen by multistage random sampling with gender as a layer. There was significant difference between female and male in knowledge, religiosity value, and attitude in reading halal label, whereas the behavior in reading label had no significant difference. Age, religiosity value, and attitude were found affected significantly behavior of reading halal label on food products.